Ketepatan Pukulan Smash pada Siswa Putra Ekstrakurikuler Bulutangkis di SMP Negeri 3 Lamongan - Hamka Arizzi; Arif Kustoro (Jurnal Multidisiplin Madani, 2022)
The accuracy of smash in badminton extracurricular at SMP Negeri 3 Lamongan still varies. This study aims to determine the accuracy of the badminton extracurricular male students' smash at SMP Negeri 3 Lamongan in 2020/2021. This type of research is descriptive quantitative with data collection techniques using tests and measurements. The research population was male students in extracurricular badminton at SMP Negeri 3 Lamongan, totaling 12 students who were taken using a total sampling technique. Data analysis using SPSS version 20 software application. The results of this study indicate that the accuracy of the badminton extracurricular male students' smash hits at SMP Negeri 3 Lamongan is in the "very poor" category of 8.33% (1 student), "less" of 0.0 % (0 students), "enough" at 33.33% (4 students), "good" at 41.66% (5 students), "very good" at 16.66% (2 students).